Investigation of the Prevalence of Infectious Myonecrosis Virus (IMNV) from 2022 to 2023 - Ruidong XU; Jitao XIA; Ping LI; Xingtong YU; Liang YAO; Wenqiang LI; Tianchang JIA; Qingli ZHANG (Progress in Fishery Sciences)
Infectious muscle necrosis (IMN) caused by infectious myonecrosis virus (IMNV) broke out for the first time in Chinese shrimp in 2020, causing substantial economical loss to the shrimp farming industry. To understand the prevalence of Chinese IMNV in recent years, an epidemiological survey of IMNV was conducted in major Chinese shrimp farming areas between 2022–2023. Samples were analyzed using molecular biology and histopathology. A total of 829 samples were collected from Shandong, Jiangsu, Zhejiang, Hainan, Tianjin, Guangxi, Fujian, and Hebei. These samples included major farmed shrimp species, such as Penaeus vannamei, P. japonicas, P. chinensis, and Macrobrachium rosenbergii, as well as live feed, other aquatic economic species, and culture water. TaqMan real-time quantitative fluorescence RT-PCR (TaqMan RT-qPCR) was used for molecular detection. The skeletal muscle of diseased shrimp exhibited the typical plaque or diffuse white necrosis symptom of IMNV infection. IMNV was detected in major farmed shrimp species such as P. vannamei, P. japonicus, and P. chinensis. The positive samples were mainly distributed in Shandong, Hebei, Tianjin, and other provinces or cities around the Bohai Sea. In addition to farmed shrimp, IMNV-positive shrimp live bait (mainly Artemia) and offshore seawater filtered close to the farm was also detected. The IMNV-positive rates of samples collected in 2022 and 2023 were 6.27% (23/367) and 15.80% (73/462), respectively. The IMNV-positive TaqMan RT-qPCR samples were further analyzed using histopathological and in situ hybridization methods. The characteristic coagulation necrosis of IMNV infection was found in the white muscle tissue sections of the ventral and caudal segments of the diseased shrimp, with a clear blue-violet hybridization signal of the IMNV probe in the muscle tissue with pathological damage. The results of this study indicated a high positive rate of IMNV in cultured shrimp, biological live bait, and offshore seawater in many Chinese provinces between 2022–2023. Detection, monitoring, and early warning of IMNV infection in the shrimp farming process should be strengthened to reduce the risk of further spread and IMN epidemics.